The Practice of Changing the Status of Change of Waqf Property in the Islamic Social Economic View - ., Muthoifin; Yusran, Qaid Qushayyi; ., Masithoh; ., Nuha; ., Waston; Nirwana, Andri (Journal of Ecohumanism, 2024)
The purpose of this study is to reveal and analyze the practice of changing the exchange status of waqf assets in the view of the Islamic social economy. This type of research is included in qualitative research, which is derived from interviews and data observation. The source of this research data consists of primary data sources, namely researchers directly conduct interviews with the parties concerned in the process of exchanging waqf property at the At-Taqwa mosque, researchers also use secondary data sources, namely books, articles, and other reference materials. The results of the study explained that in the case of exchanging waqf property at Masjid At-Taqwa by Government Regulation Number 28 of 1977 and Law Number 41 of 2004. As for the aspect of Islamic Law, in the opinion of Imam Hanafi, if the waqf property can no longer provide benefits, it can be exchanged or replaced. On the contrary, according to the Shafi’iyah and Maliki Schools, it forbids all forms of exchange and replacement of waqf property under any circumstances. And according to Hanafiyah any form of exchange or replacement of all waqf objects depends on the power of the wakif at the time the pledge is pronounced by the wakif. The originality/novelty of this study offers originality by examining how changes in the status of waqf assets can affect people’s welfare, both in terms of economics and society. In Islam, waqf is not only seen as charity but also as an economic instrument that can empower the community. Thus, a change in the status of waqf assets, for example from waqf land to commercial property, can have a significant impact on local economic empowerment.